Dosimetric Predictors of Acute and Chronic Alopecia in Primary Brain Cancer Patients Treated With Volumetric Modulated Arc Therapy - Scoccianti, Silvia; Simontacchi, Gabriele; Greto, Daniela; Perna, Marco; Terziani, Francesca; Talamonti, Cinzia; Teriaca, Maria Ausilia; Caramia, Giorgio; Lo Russo, Monica; Olmetto, Emanuela; Delli Paoli, Camilla; Grassi, Roberta; et al. (Frontiers in Oncology, 2020)
Purpose To determine dose constraints that correlate with alopecia in patients treated with photon-based Volumetric Modulated Arc Therapy (VMAT) for primary brain tumors. Methods During the treatment planning process, the scalp was drawn as a region of interest. Dose received by 0.1 cc (D0.1cc), mean dose (Dmeanscalp), volumes receiving different doses (V16Gy, V20Gy, V25Gy, V30Gy, V35Gy, V40Gy, and V43Gy) were registered for the scalp. Alopecia was assessed according to Common Terminology Criteria for Adverse Events (CTCAE) v4.0. Receiver operating characteristics (ROC) curve analysis was used to identify parameters associated with hair-loss. Results One-hundred and one patients were included. At the end of radiotherapy (RT), 5 patients did not develop alopecia (Dmeanscalp 3.1 Gy). The scalp of the patients with G1 (n=11) and G2 (n=85) alopecia received Dmean of 10.6 Gy and 11.8 Gy, respectively. At ROC analysis, V16Gy ≥16.7 cc and V20Gy ≥5.2 cc were the strongest predictors of acute alopecia risk. Chronic hair-loss assessment was available for 74 patients: 92.8% completely recovered from alopecia. Median time to recovery was 5,9 months. The actuarial rate of hair regrowth was 98.1% at 18 months after the end of RT. At ROC analysis, V40Gy ≥5.4 cc and V43Gy ≥2.2 cc were the strongest predictors of chronic alopecia risk. Conclusions V16Gy and V20Gy were the strongest predictors for acute hair-loss, whereas V40Gy and V43Gy predicted the risk of developing chronic alopecia. The low-dose bath typical of VMAT corresponds to large areas of acute but transient alopecia. However, the steep dose gradient of VMAT allows to reduce the areas of the scalp that receive higher doses, minimizing the risk of permanent alopecia. The application of our dosimetric findings for the scalp may help in reducing the alopecia risk and also in estimating the probability of hair-loss during patient counseling before starting radiotherapy.